Doxorubicin action on mitochondria: relevance to osteosarcoma therapy? - Armstrong, J.; Dass, Crispin (2015)
The mitochondria may very well determine the final commitment of the cell to death, particularly in times of energy stress. Cancer chemotherapeutics such as the anthracycline doxorubicin perturb mitochondrial structure and function in tumour cells, as evidenced in osteosarcoma, for which doxorubicin is used clinically as frontline therapy. This same mechanism of cell inhibition is also pertinent to doxorubicin's primary cause of side-effects, that to the cardiac tissue, culminating in such dire events as congestive heart failure. Reactive oxygen species are partly to blame for this effect on the mitochondria, which impact the electron transport chain. As this review highlights, there is much more to be learnt about the mitochondria and how it is affected by such effective but toxic drugs as doxorubicin in the hope that cancer treatment can be aided by finding ways to preserve mitochondrial number and function in normal cells.